THEORETICAL STUDY OF MENTAL HEALTH PROBLEMS IN PRESCHOOL CHILDREN - Djalolova Mohinur (Journals Park Publishing, 2023)
The article describes the psychological health of the children of the preschool educational organization and their problems.
Keywords: article, child mental health, program, problem, essence, psychological characteristic, concept.